FOVELASS: A Randomised Trial of Endovenous Laser Ablation Versus Polidocanol Foam for Small Saphenous Vein Incompetence. (March 2023) - Hamel-Desnos, Claudine; Nyamekye, Isaac; Chauzat, Bertrand; Gracia, Sébastien; Josnin, Matthieu; Abbadie, Fabrice
Abstract : Objective: To compare the outcomes of ultrasound guided foam sclerotherapy (UGFS) and endovenous laser ablation (EVLA) to treat isolated small saphenous vein (SSV) incompetence in a multicentre randomised controlled study (RCT; ClinicalTrials.gov identifier: NCT05468450). Methods: Patients aged ≥ 18 years undergoing isolated SSV treatment (reflux > 0.5 seconds) were randomised to UGFS or EVLA. Patients treated with UGFS were allowed one additional truncal treatment at six weeks. Tributary treatments (phlebectomy or sclerotherapy) were permitted after six months. Participants were assessed at eight days, six months, and one, two, and three years. The primary endpoint was the absence of SSV reflux (> 0.5 seconds). Secondary outcomes included clinical scores and quality of life (QoL) scores. All analyses were done by intention to treat. Results: Of 1 522 screened patients, 161 were randomised to UGFS ( n  = 82) and EVLA ( n  = 79). Only 3% of patients who received UGFS had the second (allowed) treatment and 86% of patients completed the three year study. Forty-one and 19 tributary treatments (by sclerotherapy) were performed in 27 UGFS patients (33%) and 15 EVLA patients (19%), respectively. The complete absence of reflux at three years was significantly better after EVLA (86%) than after UGFS (56%) (odds ratio [OR] 5.36, 95% confidence interval [CI] 2.31 – 12.44; risk ratio 1.59, 95% CI 1.26 – 2.01). Two deep vein thromboses (DVTs; one femoropopliteal and one gastrocnemius) and one endovenous heat induced thrombosis occurred in the EVLA group. Seven DVTs were seen in the UGFS group, including two partial popliteal DVTs and five gastrocnemius vein thromboses (four asymptomatic and incidental on day 8 screening). At three years, there was no difference between groups for the following: rate of visible varices ( p  = .87), revised Venous Clinical Severity Score ( p  = .28), and QoL ( p  = .59). Patient satisfaction scores were high in both groups (median score: EVLA 97/100 and UGFS 93/100; p  = .080). Symptoms were significantly improved in both groups. ( p < .001) Conclusion: Technical success was better for EVLA than for UGFS three years after SSV treatment. This agrees with studies that have reported on these treatments in the great saphenous vein. However, improvements in clinical outcome were similar for both groups.